Body piercing saved my life : inside the phenomenon of Christian rock - Beaujon, Andrew (Cambridge, MA : Da Capo Press, 2006)
A chronicle of modern-day Christian rock music profiles some of the most successful Christian rock bands and looks at the subculture that they have spawned, including extreme teen Bibles, skateboarding ministries, and nightclubs.
I swear -- No more LSD for me (I met the man from Galilee) -- Christian rock lifers #1: Doug Van Pelt -- More than just a song -- The baffled king composing hallelujah -- Christian rock lifers #2 : Steve Taylor -- Clarity -- Drinking blood out of skulls, living high in the kingdom of death, and a new way to be Christian -- Christian rock lifers #3 : Jay Swartzendruber -- Salt and Light, Inc. -- If we are the body -- Christian rock lifers #4 : Bill Hearn -- Black and white in a gray world -- Christian rock lifers #5 : Mark Salomon -- To be mad for my king -- Just like heaven.
Includes bibliographical references (p. 275-276) and index.
Keywords: Christian rock music -- History and criticism; Rock music -- Religious aspects -- Christianity